2016
DOI: 10.1007/s00234-016-1668-z
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted coiling of intracranial aneurysms located on small vessels: midterm results with the LVIS Junior stent in 40 patients with 43 aneurysms

Abstract: The LVIS Junior stent appears safe and effective for endovascular treatment of wide-neck intracranial aneurysms located on small vessels. Midterm results show high rates of adequate and stable occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 33 publications
3
29
1
3
Order By: Relevance
“…Alghamdi et al found similar results in a smaller series, in which the mean distal vessel diameter was 1.9 mm. In their study one case of 43 aneurysms treated had symptomatic intra-stent stenosis, which occurred at 6 months after the patient stopped their Plavix and aspirin 12. In our series, we had no cases of delayed complications.…”
Section: Discussionmentioning
confidence: 47%
“…Alghamdi et al found similar results in a smaller series, in which the mean distal vessel diameter was 1.9 mm. In their study one case of 43 aneurysms treated had symptomatic intra-stent stenosis, which occurred at 6 months after the patient stopped their Plavix and aspirin 12. In our series, we had no cases of delayed complications.…”
Section: Discussionmentioning
confidence: 47%
“…Thus, surgeons have recently been using the Leo Baby and LVIS Jr stents in small cerebral arteries. However, according to 2 case series reported by Aydin et al 11 and Alghamdi et al, 10 thromboembolic events and in-stent stenosis are also not negligible in the deployment of the LEO Baby and LVIS Jr stents in small cerebral arteries. In addition, the LEO Baby and LVIS Jr stents have not been approved for aneurysm treatment in our country.…”
Section: Discussionmentioning
confidence: 97%
“…Previous series have reported low rates of deployment failure and ease of navigability with the LVIS Jr device [20][21][22][23]. Conrad et al [24] described the first 2 cases of Y-stenting with the LVIS Jr stent for the treatment of basilar tip aneurysms.…”
Section: Discussionmentioning
confidence: 99%